Analisis Bentuk Dan Struktur Musik Programa Danse Macabre Karya Camille Saint-Saens - M. Ridham Nur; Yensharti Yensharti (SENDRATASIK UNP, 2021)
The study aims to analyze the shape and musical structure of Camille Saint-Saens's "Danse Macabre" programa, which looks at the extra elements of musicals and Intra musicals as a whole. This study uses a musical approach and the results are qualitative. The main instruments in this study are the researchers themselves. Data collection techniques are done by means of library studies and observations. The steps to analyze data are to collect data, describe data, analyze and make conclusions. The results showed that Danse Macabre is a free form of music composition in which this form of music is irregular/bound to any form of music seen working on melodies that flow just like that based on the story the composer describes can be seen based on the extramusical and intra musical elements.  The integrity of Danse Macabre's programa music work is formed from the Intro section, part A, part B, part A1, part A2, part B1, part B2, part A3, part C, part C1, part A+B, and the Coda section with the kadens on the last two seasons. Introduction tells the story of the midnight time played by Harp, resulting in the sound of clocks that signify the day at exactly 00:00 or midnight and the Grimp Reaper begins summoning ghosts to party and dance.